Surfactant Properties of Humic Acids Extracted from Volcanic Soils and Their Applicability in Mineral Flotation Processes - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C (Academic Press, 2018)
Surface Tension (ST) of water solutions of humic acids extracted from volcanic ash derived soils (soil humic acids, S-HA), were measured under controlled conditions of pH (13.0), temperature (25 °C) and ionic strength (NaOH 0.1M) to establish the Critical Micellar Concentration (CMC). All S-HA were characterized by elemental analysis, acid-base titration, Transmission Electronic Microscopy (TEM) micrographs, isoelectric point (IEP) and solid state 13C-NMR. After that, these humic acids were evaluated as potential biomaterials to be used in mineral flotation processes, where a series of experiments were conducted at different S-HA and molybdenite ratio (from 0.2 to 50 g ton−1) establishing the IEP of all resultant materials. The use of solid state 13C-NMR enabled the following sequence of intensity distribution areas of S-HA to be established: O/N Alkyl>Alkyl C>Aromatic C>Carboxyl. The experimental values of ST and the calculated CMC (ranging from 0.8 to 3.3 g L−1) revealed that for S-HA no relationship between the abundance groups and their behavior as surfactant materials was observed. In relation with IEP determined for all materials, the highest surface charge, which can be useful for flotation processes, was obtained with 0.2 g of S-HA per ton of molybdenite. Additionally, TEM studies confirm the formation of pseudoaggregates for all the S-HA considered. Finally, the S-HA could be considered as an alternative to chemical products and commercial humic acids materials in mineral flotation processes. © 2018 Elsevier Ltd